PENGARUH PEMBERIAN FOSFOR DAN UMUR PANEN TERHADAP PERTUMBUHAN DAN PRODUKSI PEGAGAN (Centella asiatica (L.) Urb.) - Mirna Sari; J. A. Napitupulu J. A. Napitupulu; Ratna Rosanti Lahay (Universitas Sumatera Utara, 2013)
The Effect of Phosphor Application and Harvesting Time to Growth and Production of IndianPennywort (Centella asiatica (L.) Urb.). Indian Pennywort has long been used as traditionalmedicine and potential to be expanded. Until now Indian Pennywort harvested from natural, then it istime to cultivated to supply the needs of medicine industry that continues to increase. One that can bedone to obtain the raw materials with good quality and sustainable is the use of phosphor which canincrease the content of bioactive compounds of Centella asiatica and proper harvesting time. Thisresearch is aim to find out the effect of phosphor application and harvesting time to growth andproduction of Indian Pennywort at Syahmad village, Lubuk Pakam Sub-district, Deli Serdangregency about 11 m above sea level on January – July 2012 by using Randomized Block Design forgrowth variable which phosphor application as single factor with 9 blocks and for component ofbiomass production variable used by Split Plot Design with factors, they are harvesting time as themain plot (8,10,12 weeks) dan phosphor application as the sub plot (0,18,36,54 kg P2O5/ha). Theparameters observed were leave number, number of stolon, fresh weight per sample and per plot, dryweight per sample and per plot. The results showed that phosphor application and harvesting timenot showed significant effects on any parameters. Interaction between phosphor application andharvesting time not showed significant effects on any parameters.Keywords : phosphor application, harvesting time, Centella asiatica